2016
DOI: 10.1371/journal.pone.0157233
|View full text |Cite|
|
Sign up to set email alerts
|

Dissecting the Effects of Ischemia and Reperfusion on the Coronary Microcirculation in a Rat Model of Acute Myocardial Infarction

Abstract: BackgroundMicrovascular injury (MVI) after coronary ischemia-reperfusion is associated with high morbidity and mortality. Both ischemia and reperfusion are involved in MVI, but to what degree these phases contribute is unknown. Understanding the etiology is essential for the development of new potential therapies.Methods and FindingsRats were divided into 3 groups receiving either 30 minutes ischemia, 90 minutes ischemia or 30 minutes ischemia followed by 60 minutes reperfusion. Subsequently hearts were ex-viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Firstly, the integrity and functionality of the endothelial cells (EC) after a myocardial infarction (MI) were evaluated in a rodent model of MI by determining nuclear damage, cell-to-cell connections and endothelium permeability. In consonance with our results, EC injury post-MI began during the ischaemic conditions, reaching its maximum after reperfusion [8]. Secondly, EC dysfunction plays a pivotal role in microvascular obstruction (MVO), which is a strong long-term predictor of mortality post-MI.…”
supporting
confidence: 89%
“…Firstly, the integrity and functionality of the endothelial cells (EC) after a myocardial infarction (MI) were evaluated in a rodent model of MI by determining nuclear damage, cell-to-cell connections and endothelium permeability. In consonance with our results, EC injury post-MI began during the ischaemic conditions, reaching its maximum after reperfusion [8]. Secondly, EC dysfunction plays a pivotal role in microvascular obstruction (MVO), which is a strong long-term predictor of mortality post-MI.…”
supporting
confidence: 89%
“…This is consistent with studies reporting that IMH is associated with larger infarcts sizes, decreased myocardial salvage and, impaired left ventricular function in patients showing ST-elevation myocardial infarction (STEMI) and was associated with increased adverse cardiovascular events [ 36 , 37 ], however the small sample size in this study was insufficient to extrapolate any significant findings from this cohort and as such these specimens were excluded from all subsequent experiments. The pathogenesis of IMH remains unknown, however it has been suggested that the microvascular blockage of the vasculature during reperfusion injury decreases the integrity of the vascular walls, while reperfusion aggravates this permeability and enhances endothelial leakage into the infarcted tissue [ 38 ]. Nonetheless, 4-MetT failed to decrease the infarct size irrespective of the presence or absence of IMH.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were stained with uranyl acetate (for 10 min) and lead citrate (for 5 min), and observed using a transmission electron microscope (H-7650, Hitachi, Tokyo, Japan) at an accelerating voltage of 80 kV. The quantification of TEM images was performed by referring to previous publications 60 , 61 . Briefly, 20 randomly selected cell-cell contact sites were captured, and the number of desmosome-like structures and their length in each contact sites were measured in a blind manner.…”
Section: Methodsmentioning
confidence: 99%